Rhetorical structure of the Arabic patent abstracts - Manal Mahmoud Alzarieni,; Intan Safinaz Zainudin,; Norsimah Mat Awal,; Mohamed Zain Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Patent abstracts function as an essential part of patents, in which drafters summarize their invention and try to persuade the evaluators to accept their invention. These abstracts also have a crucial function as a useful alternative tool for effective and quick information retrieval. However, there is a scarcity of work on how these abstracts are constructed in Arabic context despite a considerable number of studies in different languages. This study, therefore, examines the rhetorical structure of 60 patent abstracts written in Arabic by Arabicspeaking drafters in the field of Human Necessity (HN) _ one of the eight classifications that includes patents related to social life_following Swales' (1990) Create a Research Space (CARS) model. The results revealed that Arabic patent abstract section consists of five obligatory moves and an optional one. Based on the genre analysis conducted, a proposed rhetorical move/step model which may be useful for patent drafters is developed. These findings are useful for Arabic-speaking drafters and novice inventors for a better understanding of the rhetorical structure commonly applied in their drafting of patent abstracts. A better understanding of how patent abstracts are drafted can improve not only their drafting skills to meet the expectations of the target discourse community, but also the chance for successful patent grants.